2020
DOI: 10.1016/j.ijfoodmicro.2020.108667
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium fujikuroi species complex in Brazilian rice: Unveiling increased phylogenetic diversity and toxigenic potential

Abstract: Fusarium fujikuroi species complex (FFSC) species are commonly encountered infecting rice, but knowledge of the diversity and toxigenic potential of the species is lacking in Brazil, the largest rice-producing country outside Asia. One hundred FFSC isolates obtained from national rice were identified using morphology and phylogeny of TEF, CAL and TUB genes. Eight previously known and one new phylogenetic species were identified. Three species accounted for around 60% of the strains: F. fujikuroi (n = 23), F. p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 57 publications
1
8
1
Order By: Relevance
“…In this study, Fusarium was not recovered from any of the food samples, which agrees with findings from two previous studies conducted in Nigeria on rice [ 2 ] and pupuru [ 12 ]. Conversely, this finding from the present study contradicts other available reports [ 3 , 34 , 39 , 40 ] indicating several Fusarium species in grains, including rice and maize. Penicillium was the second most predominant genus in the food samples, occurring in all the sample types and mostly in maize and pupuru.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, Fusarium was not recovered from any of the food samples, which agrees with findings from two previous studies conducted in Nigeria on rice [ 2 ] and pupuru [ 12 ]. Conversely, this finding from the present study contradicts other available reports [ 3 , 34 , 39 , 40 ] indicating several Fusarium species in grains, including rice and maize. Penicillium was the second most predominant genus in the food samples, occurring in all the sample types and mostly in maize and pupuru.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, Fusarium was not recovered from any of the food samples, which agrees with findings from two previous studies conducted in Nigeria on rice [2] and pupuru [12]. Conversely, this finding from the present study contradicts other available reports [3,34,39,40] that reported several Fusarium species in cereals including rice and maize. Penicillium was the second most predominant genus in the food samples, occurring in all the foods and mostly in maize and pupuru.…”
Section: Discussionsupporting
confidence: 88%
“…PCRs were performed using the recommended regions for each genus, i.e., tub 2, ef -1 α , and its for Fusarium [ 42 , 43 ] and tub 2, cam , its and rpb 2 for Penicillium [ 44 ]. PCR was performed with an initial denaturation of 95 °C for 4 min, followed by 35 cycles of 95 °C for 30 s ( its and ef -1 α ) or 94 °C for 1 min ( rpb 2, tub 2 and cam ), annealing at 55 °C ( its ), 58 °C ( ef -1 α ) for 30 s, 47 °C ( rpb 2), 58 °C ( tub 2) or 50 °C ( cam ) for 1 min, initial extension at 72 °C for 30 s ( its ) or 1 min and at 72 °C for 10 min on the final extension.…”
Section: Methodsmentioning
confidence: 99%
“…The nucleotide sequence datasets were constructed using tub 2 and ef -1 α for Fusarium [ 42 , 43 ], or tub 2, cam , its and rpb 2 for Penicillium [ 44 , 45 ] from the two isolates characterized here, and representative isolates of the Fusarium or Penicillium. To test possible topological incongruences, phylogenetic trees were individually obtained from each genomic region.…”
Section: Methodsmentioning
confidence: 99%